2001
DOI: 10.1107/s0021889801001157
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of grazing-incidence small-angle X-ray scattering data taken above the critical angle

Abstract: The equations taking into account refraction at the sample surface in grazing-incidence small-angle X-ray scattering (GISAXS) when the angle between the incoming beam and the sample surface is slightly larger than the critical angle are derived and discussed. It is demonstrated that the refraction of both the incoming and the scattered beam at the sample surface affects the GISAXS pattern and that, when a planar bidimensional detector perpendicular to the incoming beam is used, the effect depends on the azimut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2003
2003
2006
2006

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Generally speaking, one has to deal not only with the incoming, but also with the reflected X-ray beam (Martorana et al, 2001). This means that the Born approximation is generally not valid in this case.…”
Section: Nanostructured Surfaces and Thin Layers -Gisaxsmentioning
confidence: 99%
“…Generally speaking, one has to deal not only with the incoming, but also with the reflected X-ray beam (Martorana et al, 2001). This means that the Born approximation is generally not valid in this case.…”
Section: Nanostructured Surfaces and Thin Layers -Gisaxsmentioning
confidence: 99%
“…In principle, these data must be corrected for refraction and reflection effects related to the experimental geometry. [10][11][12] However, for the present case, corrections for refraction and incident beam normalization vary negligibly across the q range of interest. Also, with an incidence angle of 0.35°, the entire ALD film thickness is sampled, and the correction for the sampling volume is calculated to vary by less than 6%.…”
mentioning
confidence: 95%
“…Complete experimental details of GISAXS studies may be found elsewhere. [10][11][12] Specular reflected intensity was measured with the incident beam collimation and linear detector slits set to equal angles of grazing incidence and specular reflection. The intensity was measured as a function of angle over the range from 0°to 6°, corresponding to q values perpendicular to the substrate of 0 -10 nm −1 .…”
mentioning
confidence: 99%
“…2b). The 2y 0 angle is determined from the scattering geometry and refraction indexes (n i ) for a given material [11]. The second effect, which also arises due to different refraction indexes, is the transmission coefficient for exiting beam, which varies depending on the incidence angle.…”
Section: Resultsmentioning
confidence: 99%